Patient Outcomes of Non-Operative Versus Operative Management of Humeral Shaft Fractures: A Randomized Controlled Trial - Badal Khan, Mir Behram Khan, Khurram Shahzad Shahwani, Eid Muhamad Mandokhail, Muhamad Bakhsh Shahwani, Sagheer Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the non-surgical versus surgical outcomes in individuals who suffered from humeral shaft fractures. Methods: A randomized controlled trial was undertaken at the Department of Orthopedics Bolan Medical College Hospital Quetta, Pakistan between 09-March-2019 to 08-October-2019. A total number of 248 patients who presented with humeral shaft fractures having age 20-60 years were included in this study. Eligible patients were randomly grouped into two equal sets. Group I: were allotted to patients in whom non-operative management of humeral shaft fractures was done. In group II patients: operative management was done. Surgical outcomes were noted in terms of delayed union and radial nerve palsy. Study outcomes were noted after 1 month of principal procedure. Results: The mean age of individuals included in this study was 45.46±9.64 years. Mean body mass index (BMI) of patients was 25.44±4.63 kg/m2. Mean duration of fracture to surgery was 8.80±8.07 days. There were 169 (68.15%) male patients and 79 (31.85%) female patients. Delayed union was found in 27 (21.80%) patients in non-operative groups versus 19 (15.30%) in patients who underwent operative management (p-value of 0.191). On comparison of frequency of radial nerve palsy between the groups, radial nerve palsy was found in 12 (9.70%) patients in non operative group versus 16 (12.90%) in patients in operative group (0.422). Conclusion: The study revealed that the non-surgical management of humeral shaft fractures gives outcomes that are comparable to operative management. We did not find any evidence of significant difference in the frequency of delayed union and radial nerve palsy between the groups. Keywords: humeral shaft fractures, operative management, non-operative management.